EFEKTIFITAS TEKNIK RELAKSASI GENGGAM JARI (FINGER HOLD) DAN RELAKSASI BENSON TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST OPERASI SECTIO CAESAREA (Nursing Care Journal, 2022)
Sectio caesarea is an artificial birth process that is carried out surgically by making an incision in the abdominal wall and the mother's uterine wall. The purpose of this study was to determine the differences in the effectiveness of finger hold relaxation techniques and Benson relaxation techniques on changes in pain intensity in patients with postoperative Sectio Cesarea at Roemani Muhammadiyah Hospital Semarang. This research method uses a quantitative method with a Quasy Experimental Pre test and Post test without control design. The population in this study were all mothers who performed postoperative caesarean section as many as 42 respondents, with the number of samples that had met the inclusion criteria as many as 30 respondents. The instruments used in this study were observation sheets, NRS (Numeric Rating Scale) scales and SOP sheets for finger grip relaxation and Benson relaxation. The results of the study using Man-Whitney analysis showed that the p value was 0.036 (<0.05), which means that there is a significant difference between the group of respondents who were given Finger Hold relaxation and the group that was given Benson relaxation. The results of the study using the NGain Score test found that the finger grip relaxation technique was more effective in reducing the intensity of post SC pain with a result of 84.00 or 84% which was included in the effective category. The conclusion of this study is that there are differences in the effectiveness of finger hold relaxation techniques and Benson relaxation on reducing pain intensity in postoperative sectio caesarea patients at RS Roemani Muhammadiyah Semarang.